2015
DOI: 10.7150/ijbs.12248
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Hgs Deficiency Leads to Impaired Esophageal Motility

Abstract: As a master component of endosomal sorting complex required for transport proteins, hepatocyte growth factor-regulated tyrosine kinase substrate (Hgs) participates multiple cellular behaviors. However, the physiological role of Hgs in smooth muscle cells (SMCs) is by far unknown. Here we explored the in vivo function of Hgs in SMCs by using a conditional gene knockout strategy. Hgs deficiency in SMCs uniquely led to a progressive dilatation of esophagus with a remarkable thinning muscle layer. Of note, the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To investigate the role of Hgs in cerebrovascular development, we bred Hgs flox/flox mice 32 with SP-A-Cre transgenic mice, 34–36 in which the Cre recombinase was specifically expressed in brain ECs beginning at E11.5. No obvious difference was observed among littermate wild type, Hgs flox/flox , and SP-A-Cre; Hgs flox/+ (hereafter referred to as control) mice in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of Hgs in cerebrovascular development, we bred Hgs flox/flox mice 32 with SP-A-Cre transgenic mice, 34–36 in which the Cre recombinase was specifically expressed in brain ECs beginning at E11.5. No obvious difference was observed among littermate wild type, Hgs flox/flox , and SP-A-Cre; Hgs flox/+ (hereafter referred to as control) mice in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Mice carrying floxed Hgs alleles 32 and SP-A-Cr e transgenic mice 34–36 have been reported previously. Genotypes of the offspring were determined by PCR using specific primers as follows: Hgs ; 5′-CCTGGTGTCCTTGGATCTCCT-3′ and 5′-GAGCCACTCTTGTAGCCTTGC-3′, Cre ; 5′-GCCTGCATTACCGGTCGATGC-3′ and 5′-CAGGGTGTTATAAGCAATCCC-3′.…”
Section: Methodsmentioning
confidence: 97%
“…TNF-α produced by macrophages and immune cells stimulates neutrophils to produce large amounts of ROS, leading to peroxidation of the esophageal mucosa (14). Moreover, studies have found that the increased levels of inflammatory factors are important factors leading to esophageal peristalsis disorder (15), and TNF-α can also promote the development of RE into Barrett's esophagitis to some extent (16). In the present study, the levels of serum IL-1β, IL-8 and TNF-α were the highest in grade III RE group, followed by grade II RE group, grade I RE group and NERD group (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte growth factor-regulated tyrosine kinase substrate (HGS) is a major component of the ESCRT-0 complex, which functions in initiating the ESCRT pathway through recognizing ubiquitylated cargo and recruiting the other ESCRT components [10]. HGS has been revealed to function in tumor metastasis [13,14], neurodegeneration [15,16], as well as the esophageal motility maintenance [17]. HGS has a distinct function in transporting low-density lipoprotein-derived cholesterol from the endosomes to the endoplasmic reticulum [18], a process that is tightly associated with lysosomal functions [19], suggesting that HGS might play a role in the maintenance of lysosomal homeostasis.…”
Section: Ivyspringmentioning
confidence: 99%
“…To obtain mice with targeted deletion of Hgs in the heart, homozygous mice for the floxed Hgs [17] allele were bred with α-MHC-Cre transgenic mice [20], in which the expression of Cre recombinase is driven by the α-MHC promoter. Mice were kept on a mix C57BL/6J X 129/SV background.…”
Section: Animalsmentioning
confidence: 99%